2019
DOI: 10.18388/abp.2019_2891
|View full text |Cite
|
Sign up to set email alerts
|

Cladonia uncialis as a valuable raw material of biosynthetic compounds against clinical strains of bacteria and fungi

Abstract: Cladonia uncialis is a lichen species with confirmed antibacterial activity and whose genome has been recently sequenced, enabling first attempts in its functional characterization. In this work, we investigated activity of the C. uncialis acetone extract (CUE) and usnic acid (UA) enantiomers against ten clinical microbial strains causing skin infections. The results showed that CUE, containing (–)-UA and squamatic acid, assayed at the same concentrations as UA, was noticeably more active than (–)-UA alone, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…According to Manojlović et al [10], salazinic acid was the dominant compound in acetone extract from P. sulcata. Other works indicated that evernic acid and (−)-usnic acid were the important components of acetone extracts of E. prunastri [6,38] and of C. uncialis [22,39], respectively.…”
Section: Discussionmentioning
confidence: 98%
“…According to Manojlović et al [10], salazinic acid was the dominant compound in acetone extract from P. sulcata. Other works indicated that evernic acid and (−)-usnic acid were the important components of acetone extracts of E. prunastri [6,38] and of C. uncialis [22,39], respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Nowadays, it is the most extensively investigated lichen secondary metabolite. Its numerous biological activities have been proved, e.g., antiprotozoal, anti-inflammatory, antimicrobial, antiviral, analgesic, insecticidal [ 7 ], antitumor, antipyretic, antiproliferative, antioxidant [ 8 ], photoprotective [ 6 ], cytoprotective, gastroprotective, and immunostimulatory properties [ 9 , 10 ]. Considering the above-mentioned activities, UA has found application in cosmetology, agriculture, the pharmaceutical industry, and dentistry [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of usnic acid was achieved by measuring the peak area with regards to the appropriate standard curve. Details of the analysis were described previously (Studzińska-Sroka et al 2019).…”
Section: Methodsmentioning
confidence: 99%